IFPRI at a glance - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The International Food Policy Research Institute (IFPRI) believes that by working together, the global community can sustainably reduce poverty and end hunger and malnutrition. IFPRI provides cutting-edge research and policy options on food and nutrition security to support these goals. For more than 40 years, IFPRI has collaborated with stakeholders and partners to contribute needed evidence for country- and region-led policies that help ensure that all people have access to safe, sufficient, nutritious, and sustainably grown food.